Biochemical and functional analysis of COS3A, a novel CD63-specific monoclonal antibody - Wansook S. (2017)
© 2016, Allergy and Immunology Society of Thailand. All rights reserved. Background: Monoclonal antibodies (mAbs) have become essential tools in life science research and in medicine, because of their extreme specificity. Several mAbs against leukocyte surface molecules have been generated in our laboratory. From these, mAb COS3A was selected for biochemical and functional analysis. Objective: To analyze the properties and function of the mAb COS3A. Method: Cellular distribution was analyzed by immunofluorescence staining and flow cytometry. Biochemical characterization of the molecular target of COS3A was approached by immunoprecipitation, Western blotting and amino acid sequencing using LC-MS. N-glycosidase F treatment of COS3A-precipitated protein and culture of U937 cells in the presence of tunicamycin before cell lysate preparation were used to study the glycosylation state of proteins. Phagocytosis was examined by flow cytometry. Results: MAb COS3A bound specifically to a molecule expressed on the surface of various human hematopoietic cells and cell lines but not on erythrocytes. The antigen had a molecular weight of 30-70 kDa, which was reduced to 25 kDa by elimination of N-linked glycan. LC-MS data and immunoprecipitation indicated that mAb COS3A bound specifically to the CD63 molecule. Remarkably, functional analysis demonstrated that mAb COS3A dramatically reduced granulocyte phagocytosis. Conclusions: The mAb COS3A recognized the CD63 molecule and strongly diminished granulocyte phagocytosis of E. coli, suggesting that CD63 may play a crucial role in the initial step of phagocytosis. MAb COS3A is, therefore, suitable for both biochemical and functional studies of CD63, and may be used for further study of the mechanism of phagocytosis and also in therapeutic approaches.